A comprehensive account of biomedical applications of CVD diamond coatings. (19th August 2021) - Ali, Mohsin; Ali, Faizan; Yang, Boxiong; Abbas, Akmal
Abstract: The last two decades have witnessed a massive increase in research pertaining to the wide range of use of artificial diamond films, in particular, chemical vapor deposition (CVD) diamond coatings. Exclusive attention has been given to these coatings as a result of their immense biocompatibility, biofunctionality and non-toxic properties, thereby justifying their preference over other conventional long-used biomedical materials. This review study details the deposition chemistry, growth mechanism, forms and determinants of CVD diamond coatings. The sole purpose of this review revolves around the account of potential biomedical applications of CVD diamond coatings to date. Earlier reports along with the most recent trends of employing CVD diamond films in orthopedic, ophthalmological, dental, biosensing, neuronal implant and antibacterial applications, are recapped. The consequential effects of CVD diamondsurface termination, functionalization and doping have also been explained. It is clear that although ample advancement has been made with regard to CVD coatings in the fields of tissue engineering, implantable devices, implant-body electrochemical interactions and fluidic activation, differentiation or immobilization, there is still plenty of room to exploit the full potential of this CVD diamond technology.